(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Students’ critical thinking skills in Biology instruction require further improvement, particularly regarding the analysis, evaluation, and synthesis of information. This study aimed to analyze the critical thinking skills of students taught using the Guided Discovery Learning (GDL) model versus those taught without it, focusing on the topic of the human immune system. A quantitative approach was employed using a quasi-experimental design with a non-equivalent control group. The study population consisted of 81 Grade XI students, with a sample of 54 students selected via purposive sampling: Class XI C served as the experimental group, and Class XI A as the control group. Data were collected using an essay test designed to measure critical thinking skills, which had been validated for both validity and reliability. Data analysis involved descriptive statistics, prerequisite testing, an Independent Sample T-Test, and N-Gain analysis. The results showed an average post-test score of 88.39 (N-Gain: 79.48%) for the experimental group, compared to 83.41 (N-Gain: 70.25%) for the control group. The Independent Sample T-Test yielded a Sig. (2-tailed) value of 0.004 (p < 0.05), indicating a significant difference in critical thinking skills between the two groups. Thus, GDL serves as a viable instructional alternative for enhancing students’ critical thinking skills regarding the human immune system.